การพัฒนาชุดกิจกรรมการอ่านจับใจความโดยใช้เทคนิค 5W1H เพื่อส่งเสริมการอ่าน กลุ่มสาระการเรียนรู้ภาษาไทยของนักเรียนชั้นประถมศึกษาปีที่ 6 - เพิ่มรัตน์, ณัฐพล; โภคสวัสดิ์, จันทรัสม์; สุดบนิด, อรรถชัย (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This study aimed to examine the effectiveness of a reading comprehension activity set using the 5W1H technique in the Thai language learning area. The objectives were to enhance students' reading comprehension ability through the 5W1H technique and to assess students' satisfaction with the activity set. The participants were Grade 6 students at Ban Sawang Chiang Whang School, Mueang Yasothon District, Yasothon Province. The research findings revealed that 17 students (81.00%) achieved scores of at least 80%, while 4 students (19.00%) did not meet the criteria. The effectiveness of the reading comprehension activity set using the 5W1H technique was measured at "E1/E2 = 84/87.50," which met the 80/80 standard. Additionally, the students' overall satisfaction with the activity set was at a high level ( = 4.34,  = 0.58). When considering individual aspects, the highest-rated component was the reading comprehension activity set itself ( = 4.38, = 0.59), followed by the benefits received ( = 4.30, = 0.52).   Keywords: Reading skill development, reading comprehension,  Ban Sawang Chiang Whang School, 5W1H